Comparison Of Sofosbuvir Plus Daclatsvir With Sofosbuvir Alone In Achieving Svr In Dialysis Dependent Chronic Hepatitis C Patients (Journal of Pharmaceutical Negative Results, 2023)
Introduction: According to current guidelines of Infectious Diseases Society of America (IDSA), hepatitis C of all genotypes in dialysis population is recommended to treat with Glecaprevir 300mg/ Pibrentasvir 120mg given for 8 to 16 weeks. Due to commercial unavailability of these drugs in Pakistan, we have compared two alternative regimes, Sofosbuvir+Daclatsvir and Sofosbuvir alone in HCV confirmed subjects on hemodialysis. Objective: To compare the efficacy of Sofosbuvir + Daclatasvir and Sofosbuvir alone in treating HCV patient on hemodialysis. It is a Randomized controlled trial spanned on Six months at Department of Nephrology, PIMS Islamabad.Subjects and Methods: In the present randomized controlled trial, a total of one hundred and eight (n=108) patients of either gender on hemodialysis and diagnosed as HCV positive were enrolled. All the patients were between age ranges 18 to 65 years and had an HCV RNA level of ≥100,000 IU/mL. All the enrolled patients were treatment naïve patients. All the enrolled patients were randomly divided into two groups by lottery method. Patients in Group A were given the combination of Sofosbuvir and Daclatasvir while patients in group B were treated with Sofosbuvir alone in dialysis department. The outcomes of the study were determined in terms of viral load detected at 3 months and sustained virological response (SVR) at six months.Results: There were 50.0% (n=27/54) males and 50.0% (n=27/54) females in group A and there were 53.7% (n=29/54) males and 46.3% (n=25/54) females in group B. Mean age of group A patients was 42.8 years ± 12.1 SD and mean age of group B patients was 47.2 years ± 10.7 SD. Mean duration of dialysis in group A patients was 28.3 months ± 25.7 SD and mean duration of dialysis in group B patients was 24.3 years ± 17.3 SD. In group A, 7.4% (n=4/54) had no baseline comorbidity, 5.6% (n=3/54) had hypertension, 55.6% (n=30/54) had diabetes, 1.9% (n=1/54) had IHD and 29.6% (n=16/54) had multiple comorbidities at baseline. The percentages in group B were 14.8% (n=8/54), 1.9% (n=1/54), 53.7% (n=19/54), 1.9% (n=1/54) and 27.8% (n=15/54), respectively. Three months after start of treatment, viral load was not detected in 98.1% (n=53/54) of patients in group A and 96.3% (n=52/54) of patients in group B (P=0.558). At six month after the start of treatment, SVR was achieved in 98.1% (n=53/54) of patients in group A and 96.3% (n=52/54) of patients in group B (P=0.558).Conclusions: Efficacy of treatment was found better at 3 and 6 months of treatment in patients who were treated with combination of Sofosbuvir and Daclatasvir (group A) when compared those treated with Sofosbuvir alone. The difference, however, was not statistically significant.